Wear resistance of plasma nitrided high speed steel - Kakaš, Damir; Zlatanović, Midrag (Journal of Production Engineering, 1990)
Samples fabricated from high-speed steels AT and M35 underwent plasma nitriding under varying process conditions and were subsequently tested in a "Pin-on-disc" machine to measure wear intensity and coefficient of friction. SEM micrographs taken at the sample and tool surfaces revealed that plasma nitriding, particularly under complex stress conditions, led to reduced wear intensity. The study demonstrated the close relationship between the service life of tools and the depth and microhardness distribution of the plasma-nitrided layers. Different sets of plasma nitriding parameters, each yielding distinct hardness profiles and nitriding layer depths, were utilized, and wear resistance was found to be influenced significantly by the intensity of sputtering during ion bombardment, as well as the material composition of the pins. Moreover, industrial tests on tools for cold backward extrusion demonstrated the pronounced impact of factors like stress distribution in the punch's surface zone, the microhardness of the nitrided layer, and the dimensions, shape, and distribution of these features on tool durability.